KAJIAN KERAPATAN TANAMAN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum Mill) VARIETAS BETAVILA YANG DI PANGKAS PUCUK APIKAL - Maria Klara Salli; Yosefina Lewar (Partner, 2018)
The productivity of tomato plants in East Nusa Tenggara (NTT) in 2016 reached 4.70 tons/ha, increasing by 17.66% from 2015. However, the harvested area decreased by 6.74%. Based on the above data, there is an increase in tomato productivity in NTT but still low compared to national productivity of 15.31 tons/ha. Some of the possible differences in productivity, in addition to the decline in harvested area are also caused by inadequate cultivation techniques that include plant density regulation and other cultivation measures. The purpose of this study was 1) to examine the effect of plant density on growth and yield of tomato plants cut by apical buds and 2) to obtain the best size of plant density that can increase the growth and yield of tomato plants. This study used a randomized block design with a planting distance factor consisting of 8 treatment levels with 4 replications: spacing of 50cmx40cm, 60cmx40cm, 70cmx40cm, 50cm x 50cm, 60cm x 50cm, 70cm x 50cm, 60cm x 60cm, 60cm x 60cm and 70cm x 60cm. The results showed that plant density had an effect on plant growth, namely stem diameter and number of productive branches, and influenced the yield of tomato plants namely fruit weights, plant density/spacing of 70 cm x 40 cm and 70 cm x 60 cm had the best influence on plant growth and fruit weight per plant highest (1037.19grams/plant and 907.50 grams/plant) of  betavila variety.